RELATIONSHIP BETWEEN KNOWLEDGE AND THE OCCURRENCE OF DENTAL CARIES IN SCHOOL-AGE AT SDN 2 JATIMULYA - Purwanto, Ika (Sekolah Tinggi Ilmu Kesehatan Widya Dharma Husada Tangerang, 2024)
Caries is a pathological process that starts on the external tooth surface, is limited to a certain area, occurs after tooth eruption, and causes tooth decay to produce cavities. At school age, children's health problems are very important, because school age is very vulnerable in health problems, especially dental health. This study aims to determine the relationship between knowledge and the appearance of dental caries in school-age children. The research design used in this study was descriptive analytic with a cross sectional approach. The sample amounted to 41 respondents. Univariate analysis and bivariate analysis to determine the relationship between variables. The results showed that there was a relationship between knowledge about dental caries and the occurrence of dental caries in school-age children. Advice to health workers to provide knowledge to teachers / parents / guardians of students about the benefits of the importance of early dental care to school-age children to prevent dental caries.